Challenges of the church in facing religious pluralism and its impact on church growth in Indonesia - Johanes Witoro (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This paper aims to examine the church's challenges in dealing with religious pluralism in Indonesia and its impact on church growth. This article takes a qualitative method with an emphasis on historical-grammatical interpretation. The following data collection approaches were employed in this study: To begin, interpret the biblical text grammatically-historically. Following that, perform a comparative analysis of the primary contemporary views of the unknown God (Acts 17:23). Finally, conduct a critical study in order to develop a historical reconstruction that takes into account ancient writing techniques. The purpose of this article is to classify, explore, and extract texts from the historical city of Athens, as well as to produce texts using hermeneutic principles. This research will examine various interpretations of each source in order to develop conclusions about the research conducted and its theological implications.  Acts 17:23-25 is the focus of this study. The findings of this study reveal that while the Bible preaches religious tolerance, this study demonstrates that the Church must naturally expand in accordance with God's purposes and the Word, which compels the Church to accommodate religious tolerance. The conclusion is that the church must continue to exist in order to fulfill the Lord Jesus' commandment to bring the gospel to all people (Matt. Acts 1:8), as Paul did in Athens.